Sorghum and millet workshop held in Mali - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
in-country workshop on sorghum and millet in Mali was held in Bamako, Mali, by the West African Sorghum Improvement Programme (Mali) October 1988